Testing the activitystat hypothesis: a randomised controlled trial. (December 2016) - Gomersall, S.; Maher, C.; English, C.; Rowlands, A.; Dollman, J.; Norton, K.; Olds, T.
Abstract Background It has been hypothesised that an 'activitystat' may biologically regulate energy expenditure or physical activity levels, thereby limiting the effectiveness of physical activity interventions. Using a randomised controlled trial design, the aim of this study was to investigate the effect of a six-week exercise stimulus on energy expenditure and physical activity, in order to empirically test this hypothesis. Methods Previously inactive adults (n  = 129) [age (mean ± SD) 41 ± 11 year; body mass index 26.1 ± 5.2 kg/m2 ] were randomly allocated to a Control group (n  = 43) or a 6-week Moderate (150 min/week) (n  = 43) or Extensive (300 min/week) (n  = 43) exercise intervention group. Energy expenditure and physical activity were measured using a combination of accelerometry (total counts, minutes spent in moderate to vigorous physical activity) and detailed time use recalls using the Multimedia Activity Recall for Children and Adults (total daily energy expenditure, minutes spent in moderate to vigorous physical activity) at baseline, mid- and end-intervention and 3- and 6-month follow up. Resting metabolic rate was measured at baseline and end-intervention using indirect calorimetry. Analysis was conducted using random effects mixed modeling. Results At end-intervention, there were statistically significant increases in all energy expenditure and physical activity variables according to both accelerometry and time use recalls (p  < 0.001) in the Moderate and Extensive groups, relative to Controls. There was no significant change in resting metabolic rate (p  = 0.78). Conclusion Taken together, these results show no evidence of an "activitystat" effect. In the current study, imposed exercise stimuli of 150–300 min/week resulted in commensurate increases in overall energy expenditure and physical activity, with no sign of compensation in either of these constructs. Trial registration number ACTRN12610000248066  (registered prospectively 24 March 2010)